PREPARATION FOR PALATOPLASTY SURGERY WITH AN ACRYLIC FEEDING OBTURATOR: A CASE REPORT - Christine Anita Wardaningrum; Endang Wahyuningtyas; Titik Ismiyati; Sri Budi Barunawati (Dentino : Jurnal Kedokteran Gigi, 2021)
ABSTRACTBackground: Clefts on the lips and palate are common cases to be found frequently in the field of dentistry. This gap connects the oral cavity and the nasal cavity so that it interferes with the nutritional intake in patients. The age and size of the oral cavity in patients become particular challenges for prosthetic rehabilitation. Another challenge lies at the impression procedure, because it is an essential part in the making of obturator. Objective: To provide information on the management of patient with cleft palate using feeding obturator from acrylic material. Case: A 13-months-old male patient arrived at Prof. Soedomo Gadjah Mada University Dental Hospital with his parents and was seeking for prosthetic therapy to cover the cleft on his palate because it had been muddling with food and beverage intake. Patient had undergone cheiloplasty surgery and further arranged for palatoplasty procedure. Intraoral examination exhibited a cleft extended from hard palate, soft palate, and uvula. Case management: Upper jaw impression was performed for individual tray fabrication, followed by impression procedure in an upright straight position until the patient bawled. The impression result was casted to construct an obturator using acrylic heat cure material. Fitting surface was covered with soft liner. Treatment result showed that the obturator was retentive, stable and able to assist the nutritional intake in patient. Conclusion: Acrylic feeding obturator can recover the condition in patient with cleft palate and improve nutritional intake as well as body weight to prepare patient for palatoplasty surgery.Keywords: Cleft Palate, Feeding Plate, Obturator